Assessment of Collegian Student's Awareness Regarding Drug Uses at Al- Muthanna University (Texas Journal of Medical Science, 2022)
Globally, deaths directly caused by drug use increased by 60 per cent from 2000 to 2015. People over the age of 50 accounted for 39 per cent of the deaths related to drug use disorders in 2015. However, the proportion of older people reflected in the statistics has been rising: in 2000, older people accounted for just 27 per cent of deaths from drug use disorders. About 75 per cent of deaths from drug use disorders among those aged 50 and older are linked to the use of opioids. The use of cocaine and the use of amphetamines each account for about 6 per cent; the use of other drugs makes up the remaining 13 per cent.( UNODC,2018).